CD32 Expression of Different Memory T Cell Subpopulations in the Blood and Lymph Nodal Tissue of HIV Patients and Healthy Controls Correlates With Immune Activation. (1st April 2018) - Wittner, Melanie; Dunay, Gábor A.; Kummer, Silke; Bockhorn, Maximillian; Hüfner, Anja; Schmiedel, Stefan; Degen, Olaf; van Lunzen, Jan; Eberhard, Johanna M.; Schulze zur Wiesch, Julian
Abstract : Background: Recently, CD32 has been described to be a specific surface marker of latently HIV-infected CD4 + T cells, but little is known about the frequency and distribution of CD32 expression on naive and memory CD8 + and CD4 + T cell populations in HIV patients and healthy individuals. Methods: We studied peripheral blood samples of 36 HIV-1–infected patients [23 viremic patients / 13 antiretroviral therapy(ART)–treated] and healthy individuals (n = 14) as well as cells from lymph nodes (8 HIV infected, 5 controls) using a multiparametric flow cytometry panel determining surface expression of CD3, CD8, CD4, CD45RA, CCR7, CD27, CD25, CD127, CCR5, CCR6, CXCR4, CD38, HLA-DR, TIGIT, and PD-1. Results: Overall, expression of CD32 on total peripheral CD4 + T cells between viremic HIV patients, ART-treated and healthy individuals only slightly differed (mean values 1.501%, 0.2785%, and 0.2343%, respectively). However, the level of expression was significantly higher in peripheral and lymph nodal memory CD4 + T cell subpopulations of viremic patients compared with ART-treated patients and healthy controls. CD32 + CD4 + T cells showed higher immune activation and higher expression of CXCR4 + than their CD32 − counterparts. Furthermore, expression of CD32 on total CD4 + T cells and memory T cell populations correlated with general immune activation regardless of the infection status. Conclusions: Follow-up studies will have to further evaluate CD32 as marker of latently HIV-infected CD4 + T cells since other host-related variables such as immune activation seem to influence CD32 expression regardless of the infection status. Abstract : Supplemental Digital Content is Available in the Text.